Sistem Penggajian di CV. Pusaka Bali Persada - NI PUTU ADELIA SARASWATI ERAWAN; I NYOMAN GEDE USTRIYANA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Payroll System at CV. Pusaka Bali Persada Every company really needs the role of human resources in carrying out its businessactivities and must be managed properly. Human resources function to improve theeffectiveness and efficiency of a company as a function in the company. One way to getcompeting human resources is to pay attention to the payroll system in a company. Thepayroll system itself aims to attract employees, retain employees, and motivateemployees.This research was conducted at CV. Bali Persada Heritage which is determinedintentionally. Sampling using techniques with census methods. The number of samplesis 12 respondents consisting of top managers and middle managers. This study usesqualitative descriptive analysis.The results showed that the salaries of employees at CV. Pusaka Bali Persada consistsof basic salary and benefits. CV. Pusaka Bali Persada provides basic salary by referringto the District / City Minimum Wage (UMK) that has been set by the government.Paying is done with a payroll administration system. The results of this study also showthat the determinants of payroll system in CV. Pusaka Bali Persada includes payrolltechniques, payroll procedures, payroll structure, payroll openness, government support,and payroll policies. The majority of top managers and middle managers agree with thepayroll system that has been applied by CV. Pusaka Bali Persada.